An Axiological Review of Fiqh on Production and Consumption in Modern Economic Development - Alya Rahma Falasifah; Yulada Syurfa; Ali Muhatarom; Zawawi Zawawi (SIL'AH: Jurnal Ekonomi Syariah, 2026)
This study aims to identify the axiology of fiqh regarding production and consumption in the context of the challenges posed by the development of the modern economic system. This study employs a literature review approach with descriptive qualitative analysis. The data comprises various academic literature discussing Islamic economics, production ethics, and consumption behaviour. The findings indicate that production in Islamic economics emphasises halal processes, social responsibility, environmental sustainability, and the avoidance of exploitative practices. Meanwhile, consumption in Islamic economics is based on the principles of moderation, cleanliness, morality, and social solidarity. This research contributes to strengthening the discourse on the Islamisation of the modern economic system, and is expected to provide practical fiqh guidance for producers, consumers and policymakers in applying Islamic economic practices.